Properties of Nat4, an N(α)-Acetyltransferase of Saccharomyces cerevisiae That Modifies N Termini of Histones H2A and H4 - Polevoda, Bogdan (American Society for Microbiology (ASM), 2009)
Nat4, also designated NatD, was previously shown to acetylate the N termini of histones H2A and H4, which have SGGKG and SGRGK N termini (O. K. Song, X. Wang, J. H. Waterborg, and R. Sternglanz, J. Biol. Chem. 278:38109-38112, 2003). The analysis of chimeric proteins with various N-terminal segments of histone H4 fused to iso-1-cytochrome c revealed that efficient acetylation by NatD required at least 30 to 50 amino acid residues of the N terminus of histone H4. This requirement for an extended N terminus is in marked contrast with the major N-terminal acetyl transferases (NATs), i.e., NatA, NatB, and NatC, which require as few as two specific residues and usually no more than four or five. However, similar to the other NATs, NatD is associated with ribosomes. The nat4-Δ strain showed several minor phenotypes, including sensitivity to 3-aminotriazole, benomyl, and thiabendazole. Moreover, these nat4-Δ phenotypes were enhanced in the strain containing K5R K8R K12R replacements in the N-tail of histone H4, suggesting that the lack of N-terminal serine acetylation is synergistic to the lack of acetylation of the H4 N-tail lysines. Thus, N-terminal serine acetylation of histone H4 may be a part of an essential charge patch first described for the histone H2A.Z variant in Tetrahymena species.